Pengaruh Promosi dan Fasilitas Terhadap Kepuasaan Pelanggan Pada Hotel Yasmin Karawaci Tangerang - Mahnun Masádi, Mahnun; Rozak, Abdul (Jurnal Manajemen & Pendidikan [JUMANDIK], 2024)
This research method uses quantitative methods with a descriptive approach. This type of associative research uses a quantitative approach with a population of 19088 with a sample of 100 respondents. This research uses linear regression methods, correlation coefficient, determination, t test analysis, and f test. The results of the linear regression test show that a constant of 1.857 means that if Promotion (X1) and Facilities (X2) are not considered then Customer Satisfaction (Y) will only be worth 1.857 points. The correlation coefficient obtained is 0.936, meaning that the Promotion (X1) and Facilities (X2) variables have a very strong relationship with customer satisfaction. The result of the coefficient of determination is 0.876, it can be concluded that the Promotion (X1) and Facilities (X2) variables have an effect on the Customer Satisfaction variable by 87.6%. The results of the promotion t test show that the p value is < sig 0.05 or (0.000 < 0.05). The obtained t value > t table is (23.705 > 1.984). Likewise, the facility t test shows p value < sig 0.05 or (0.000 < 0.05), obtained tcount > ttable (21.701 > 1.984). The results using the f test were obtained with a p value < sig 0.05 or (0.000 < 0.05), and the calculated f value > f table, namely (343.611 > 3.09). From the results of this research, it can be concluded that promotions and facilities have a significant influence on customer satisfaction at the Yasmin Karawaci Hotel Tangerang.